From Humility To Superior Human Beings: The Retention Of Benjang Wrestling In Paguron Dharma Pusaka Panca Indra - Naufal, Daffa Imam; Syahrial, Syahrial (Universitas Cokroaminoto Palopo, 2025)
This research aims to explain the values contained in the Benjang Wrestling performances as the basis for inheritance and efforts to defend Benjang Wrestling carried out at Paguron Dharma Pusaka Panca Indra. Indonesia, which has thousands of ethnic groups spread from the West to the East, has a diversity of arts and culture. These arts and cultures represent the thoughts and values owned by each tribe. Each tribe has its own distinctive performing arts. One of the typical performing arts in Sundanese society is Benjang. Benjang performance is a traditional wrestling performance in the Sundanese community combined with music and dance accompaniment. The musical accompaniment that accompanies the Benjang performance consists of terebang, drums, Sundanese trumpets, and kecrek. Currently, the existence of Benjang Wrestling is starting to dim in the community. This was motivated by the prohibition of Benjang Wrestling performances during the New Order period. In addition, Benjang Wrestling is less known today than other Benjang performances, such Benjang Helaran and Benjang Mask. Benjang Wrestling as a performance has a philosophical meaning contained in it. The philosophical meaning contained in the Benjang Wrestling is an important value that needs to be passed on to the next generation. This research will elaborate on the philosophical meaning in Benjang Wrestling as the basis for inheritance and explain the preservation efforts made by paguron in preserving Benjang Wrestling. The research method used is a qualitative method with an ethnographic approach. The results of the study show that the meaning contained in the Benjang Wrestling is the basis in the inheritance process that aims to create superior humans. This is a value that is maintained by the perpetrators to be passed on to the next generation.